2013
DOI: 10.1038/ncomms3100
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual judgements and chronic imaging of altered odour maps indicate comprehensive stimulus template matching in olfaction

Abstract: Lesion experiments suggest that odour input to the olfactory bulb contains significant redundant signal such that rodents can discern odours using minimal stimulus-related information. Here we investigate the dependence of odour-quality perception on the integrity of glomerular activity by comparing odour-evoked activity maps before and after epithelial lesions. Lesions prevent mice from recognizing previously experienced odours and differentially delay discrimination learning of unrecognized and novel odour p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…The reduction of 620 performance in this task was not due to inability to perform general odour discriminations as all groups 621 with odour recognition deficits were largely still able to learn novel odour pair discriminations. This is 622 in agreement with previous findings (Bracey et al, 2013) where it was also reported that transient 623 decreases in performance accuracy occur for odour recognition tasks (after nasal epithelium lesioning) 624…”
Section: Assessment Of Graded Olfactory Bulb Lesion Effects 610supporting
confidence: 89%
See 3 more Smart Citations
“…The reduction of 620 performance in this task was not due to inability to perform general odour discriminations as all groups 621 with odour recognition deficits were largely still able to learn novel odour pair discriminations. This is 622 in agreement with previous findings (Bracey et al, 2013) where it was also reported that transient 623 decreases in performance accuracy occur for odour recognition tasks (after nasal epithelium lesioning) 624…”
Section: Assessment Of Graded Olfactory Bulb Lesion Effects 610supporting
confidence: 89%
“…Results of lesioning experiments (Lu and Slotnick, 1998; McBride and 61 Slotnick, 2006;Slotnick, 2007) in the mouse olfactory bulb and from knockout mice with OSN axon 62 guidance defects (Knott et al, 2012) have been interpreted as evidence that relatively large 63 disruptions to the olfactory bulb have little effect on olfactory function (Laurent, 1999; Wilson and 64 Mainen, 2006). By contrast, other studies report conflicting results (Johnson and Leon, 2007), for 65 example that major disruptions cause deficiencies in odour recognition and discrimination, whilst 66 even minor disruptions can affect recognition (Bracey et al, 2013). 67…”
Section: Introduction 23mentioning
confidence: 99%
See 2 more Smart Citations
“…Cortical feedback onto inhibitory neurons [39,40,66] might contribute to the context-dependent reorganization described here by supressing MCs activity of incongruent stimuli. Theoretical and experimental studies suggest that odour recognition relies on matching sensory input patterns to a previously generated stimulus template that is formed by experience [67][68][69]. If the correspondence between the input and the stored template is low than the non-template information can be suppressed [64].…”
Section: Flexible Categorisation Following Learningmentioning
confidence: 99%